EUPHEMISTIC EXPRESSIONS OF THE LATE PRINCESS LADY DIANA MARRIAGE LIFE ON THE ONLINE NEWSPAPER - Yessie Aldriani (Asosiasi dosen IDEBAHASA KEPRI, 2019)
Euphemism is a more polite expression to substitute the rude expression which assume as the harsh or offensive words. This expression is often used in communication both spoken or written such as, the word ‘die’ is changed into ‘pass away’. The euphemistic expressions are also found on both printed or online media as newspaper. A newspaper has the power of influencing the reader’s mind in delivering many kinds of news or events in daily life. In this developing communication era, the preference and the use of the proper words in a newspaper is a must. The journalist is demanded to be able to deliver the news by using the polite and formal words instead of the offensive words. This research aimed to describe the use of euphemistic expressions on the online newspaper namely Express which was about the marriage life of the Late Princes lady Diana and The Prince Charles from United Kingdom. This was a descriptive research and Warren’s theory as cited in (Beizaee & Mirza, 2016) was used to analyze the use of euphemistic expressions based on semantic innovation and formal innovation found in some articles on Expressonline newspaper. The data is in the form of words and phrases and in analyzing the data, the researcher used the pragmatic referential method which interpret the meaning of euphemistic expressions based on the context. The results of this research are the types of semantic innovation used included particularization, implication and metaphor, meanwhile for the formal innovation included foreign words, derivation. The most dominant for semantic and formal innovation are implication and derivation. The researcher conclude that from the results, it can be said that the express online newspaper has done the good effort to deliver the news about the phenomenal marriage life of the late Princess Lady Diana and The Prince Charles by using euphemistic expressions so far.